STUDI KOMPARATIF PENDIDIKAN INKLUSI DAN PENDIDIKAN LUAR BIASA DALAM SISTEM PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS - Sutiono, Sutiono; Aurelia Zahra, Nasywa; Maysaroh, Fasichatul (Spektra: Jurnal Ilmu-ilmu Sosial, 2026)
Inclusive education and special education are two educational approaches that aim to provide equitable educational services for students, especially for children with special needs. The background of this research is based on the fact that many children with special needs still do not have access to proper and equal education with other children. The method used in this research is a qualitative method with a library research approach, namely by reviewing various literature sources such as books, scientific journals, and related documents that discuss the concepts, policies, and implementation of inclusive education and special education. The data obtained were then analyzed descriptively to gain a comprehensive understanding of the concepts, objectives, and application of both education systems in the educational world. The purpose of this study was to determine the concepts and characteristics of inclusive education and special education, understand their roles in providing equal educational opportunities for children with special needs, and examine the importance of implementing an inclusive education system in creating a just, humanistic, and respectful educational environment for student diversity. Thus, it is hoped that inclusive education and special education can be a solution in realizing a more inclusive and equitable education system for all children.